Automated Weaning from Mechanical Ventilation after Off-Pump Coronary Artery Bypass Grafting - Fot, Evgenia V.; Izotova, Natalia N.; Yudina, Angelika S.; Smetkin, Aleksei A.; Kuzkov, Vsevolod V.; Kirov, Mikhail Y. (Frontiers in Medicine, 2017)
Background The discontinuation of mechanical ventilation after coronary surgery may prolong and significantly increase the load on intensive care unit personnel. We hypothesized that automated mode using INTELLiVENT-ASV can decrease duration of postoperative mechanical ventilation, reduce workload on medical staff, and provide safe ventilation after off-pump coronary artery bypass grafting (OPCAB). The primary endpoint of our study was to assess the duration of postoperative mechanical ventilation during different modes of weaning from respiratory support (RS) after OPCAB. The secondary endpoint was to assess safety of the automated weaning mode and the number of manual interventions to the ventilator settings during the weaning process in comparison with the protocolized weaning mode. Materials and methods Forty adult patients undergoing elective OPCAB were enrolled into a prospective single-center study. Patients were randomized into two groups: automated weaning (n = 20) using INTELLiVENT-ASV mode with quick-wean option; and protocolized weaning (n = 20), using conventional synchronized intermittent mandatory ventilation (SIMV) + pressure support (PS) mode. We assessed the duration of postoperative ventilation, incidence and duration of unacceptable RS, and the load on medical staff. We also performed the retrospective analysis of 102 patients (standard weaning) who were weaned from ventilator with SIMV + PS mode based on physician’s experience without prearranged algorithm. Results and discussion Realization of the automated weaning protocol required change in respiratory settings in 2 patients vs. 7 (5–9) adjustments per patient in the protocolized weaning group. Both incidence and duration of unacceptable RS were reduced significantly by means of the automated weaning approach. The FiO2 during spontaneous breathing trials was significantly lower in the automated weaning group: 30 (30–35) vs. 40 (40–45) % in the protocolized weaning group (p < 0.01). The average time until tracheal extubation did not differ in the automated weaning and the protocolized weaning groups: 193 (115–309) and 197 (158–253) min, respectively, but increased to 290 (210–411) min in the standard weaning group. Conclusion The automated weaning system after off-pump coronary surgery might provide postoperative ventilation in a more protective way, reduces the workload on medical staff, and does not prolong the duration of weaning from ventilator. The use of automated or protocolized weaning can reduce the duration of postoperative mechanical ventilation in comparison with non-protocolized weaning based on the physician’s decision.